Identifying overreporting in a correctional setting: utility of the MMPI-2 restructured form validity scales - Wall, Tina D. (Criminal justice and behavior, 2015)
The current study examined the utility of the Minnesota Multiphasic Personality Inventory?2 Restructured Form (MMPI-2-RF) validity scales in a sample of incarcerated offenders. Utilizing an analogue simulation design, we compared a group of 36 inmates instructed to feign symptoms of mental illness with 56 inmates who had been referred for psychiatric treatment and completed the test under standard instructions. We also had a group of 63 inmates with no history of mental illness who completed the test under standard instructions. Our results indicated large effect sizes between the feigning and comparison groups for all the validity scales. Infrequent Responses (F-r) exhibited utility in discriminating between feigning and control inmates, whereas Infrequent Psychopathology Responses (Fp-r) and Infrequent Somatic Responses (Fs) exhibited the largest effect size in discriminating between the feigning and psychiatric inmate groups. Classification accuracy generally revealed greater specificity than sensitivity for the MMPI-2-RF validity scales.